Subgrade Stabilization with Ca (OH)2 Lime to Improve the Physical and Mechanical Properties of Soil (Case Study: The National Road Trengguli – Bts. Kab. Demak/Kudus) - Rahmadsyah Rangkuti; Ria Asih Aryani Soemitro; Dwa Desa Warnana; Trihanyndio Rendy Satrya; Yanuar Dwi Putra (Journal of Infrastructure & Facility Asset Management, 2024)
Road damage on The National Road Trengguli -Bts. Kab. Demak/Kudus in the form of cracks and collapses, the contributing factors are soft subgrade conditions and irrigations on both sides of the road. Chemical stabilization with Ca(OH)2lime can improve the soil's mechanical and physical characteristics. This research uses the addition of lime with variations of 2%, 4%, 6%, 7%, 8%, and and 10% of the soil's dry weight. Based on the standard proctor test results, the optimum mixture of 6% lime was obtained with a value of γdmax = 1.459 gr/cm3and Wopt= 28.052%. Furthermore, the original soil and 6% lime mixture were tested: sieve and hydrometer analysis, Atterberg limits, standard proctor compaction, unconfined compressive strength (UCS), laboratory CBR (soaked) and 1 cycle drying -wetting testing. At 6% lime for UCS and CBR testing, 0, 7 and 14 days of curing were conducted. The results of research on the initial soil and after 6% lime stabilization, namely the soil classification based on USCS originally included in CH, namely non-organic loamy soilwith high plasticity or fat clays to SM, namely silty sand and based on AASHTO originally included in A-7-6 clay soil to A-7-5 clay soil, from PI = 43.232% to PI = 16.213%, from CBR = 0.917% to CBR with 0, 7, and 14 days of curing are 11.463%, 14.266%, and 19.408%, from qu = 0.967 kg/cm2to qu with 0, 7, and 14 days of curing are 2.973 kg/cm2, 9.546 kg/cm2and 12.206 kg/cm2. After 1 cycle drying -wetting test, there is a decrease in qu value, namely in the initial soil of 93.004% and 6% lime stabilized soil of 73.040%.